2020
DOI: 10.1111/jam.14831
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance phenotypes and genotypes of Streptococcus suis isolated from clinically healthy pigs from 2017 to 2019 in Jiangxi Province, China

Abstract: Aims This study aimed to investigate the antimicrobial resistance (AMR) profiles and genotypes of Streptococcus suis from Jiangxi Province, China. Methods and Results A total of 314 nasal swab samples were collected from clinically healthy pigs, with a positive isolation rate of S. suis of 34·08%. Antimicrobial susceptibility testing showed that more than 80% of the isolates were susceptible to vancomycin, penicillin, minocycline and chloramphenicol. A high frequency of resistance to clindamycin, tetracycline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
6
21
0
Order By: Relevance
“…More than 80% of isolates contained at least one gene predicted to confer macrolide resistance (Palmieri et al, 2011). The presence of erm ( B ) and mef ( A ) genes are consistent with previous studies, where erm ( B ) is strongly linked with macrolide-lincosamide-streptogramin B (MLS B ) resistance and presented in 59-90% of macrolide-resistant S. suis isolates from pigs (Martel et al, 2001; Zhang et al, 2015; Tan et al, 2020). The resistant gene, erm ( T ) has been detected in S. agalactiae, S. pyogenes , and other erythromycin-resistant isolates of group D Streptococci (Chen et al, 2012; Zhang et al, 2015; Yongkiettrakul et al, 2019), our identification of erm ( T ) in this study suggests potential within-genus HGT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than 80% of isolates contained at least one gene predicted to confer macrolide resistance (Palmieri et al, 2011). The presence of erm ( B ) and mef ( A ) genes are consistent with previous studies, where erm ( B ) is strongly linked with macrolide-lincosamide-streptogramin B (MLS B ) resistance and presented in 59-90% of macrolide-resistant S. suis isolates from pigs (Martel et al, 2001; Zhang et al, 2015; Tan et al, 2020). The resistant gene, erm ( T ) has been detected in S. agalactiae, S. pyogenes , and other erythromycin-resistant isolates of group D Streptococci (Chen et al, 2012; Zhang et al, 2015; Yongkiettrakul et al, 2019), our identification of erm ( T ) in this study suggests potential within-genus HGT.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we detected tet( L ) and tet ( W ) genes, which have not often been reported in S. suis , among non-serotype 2 isolates from healthy pigs. Corresponding phenotypic resistance to tetracycline was reported in over 90% of isolates, which is consistent with global data reporting widespread resistance to tetracycline and macrolides, likely related to the prophylactic use in agriculture (Soares et al, 2014; Yongkiettrakul et al, 2019; Mourkas et al, 2020; Tan et al, 2020). AMR may play a role in increasing numbers of treatment failures (Hughes et al, 2009; Gurung et al, 2015; Yongkiettrakul et al, 2019), and in our study, despite widespread MDR, we observed phenotypic susceptibility to all three of the recommended antimicrobials used to treat clinical S. suis meningitis (penicillin, ceftiofur, and ceftriaxone) (van Samkar et al, 2015; Seitz et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Two mechanisms of resistance to tetracyclines have been characterized in S. suis: (i) efflux pumps that expel the antibiotic outside the cell and are encoded either by tet (L), tet (B), tet (K), or tet (40) genes [ 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and (ii) ribosome protection proteins, encoded by tet (O) (the most frequently described gene in S. suis ), tet (M), tet (S), tet (W), tet (O/W/32/O), or tet (O/32/O) genes [ 18 , 21 , 23 , 24 , 25 , 26 , 30 , 32 , 33 ] ( Figure 1 ).…”
Section: Mechanisms Of Antimicrobial Resistance (Amr) and Resistance Genes Found In S Suismentioning
confidence: 99%
“…The erm(B) gene is present in a variety of Gram-positive bacteria, including enterococci, streptococci, and staphylococci [35]. AR gene erm (B) served as the most frequent genotype that contributed to macrolide resistances [36]. In our study, strains 11313 and 11LB5 carry erm (B) gene and appear to be highly resistant to macrolide antibiotics spiramycin.…”
Section: Discussionmentioning
confidence: 58%